Frequency and clinical impact of hyperkalaemia within a large, modern, real‐world heart failure population - Joseph B. Muhlestein; Jennifer Kammerer; Tami L. Bair; Kirk U. Knowlton; Viet T. Le; Jeffrey L. Anderson; Donald L. Lappé; Heidi T. May (ESC Heart Failure, 2021)
Abstract Aims This analysis qualitatively describes the impact of hyperkalaemia (HK) and renin‐angiotensin‐aldosterone system inhibitor (RAASi) use on clinical outcomes in patients with heart failure (HF). Methods and results Patients were included if they were ≥18 years old; had a serum potassium result between 1 January 2003 and 3 December 2018; had ≥2 separate, non‐urgent care or emergency department encounters; and had an HF diagnosis. Criteria were met by 52 253 patients; 48 333 had sufficient follow‐up for analysis. Patients were stratified by the presence/absence of HK (serum potassium >5.0 mmol/L) (n = 31 619 and n = 20 634, respectively) and by baseline left ventricular ejection fraction (LVEF) ≤40% or >40%. Compared with patients without HK (no‐HK), those with HK had significantly higher rates of baseline cardiovascular risk factors, prior diagnoses, and greater RAASi use in both baseline and follow‐up periods. Assessed outcomes included RAASi use, rate of 3 year major adverse cardiovascular events (MACE), and individual component rates. Between baseline and follow‐up analyses, the proportion of patients on RAASi decreased by 5% in patients with HK but increased by 20% in no‐HK patients. Overall, MACE and death were consistently highest in the presence of HK without RAASi treatment (63% and 62%, respectively) and lowest in no‐HK but on RAASi (25% and 21%, respectively). After complete multivariable adjustment, these trends were consistent regardless of baseline LVEF. Conclusions In this large, real‐world HF population, HK was common and linked to baseline clinical risk factors, declining use of RAASi treatment, and an increase in future MACE, regardless of baseline LVEF. Both HK and reduced RAASi use were independent predictors of future MACE.